Praktik Jual Beli Naskah Kuno di Masyarakat - Ahmad, Nur Fauzan (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
This paper will discuss the practice of trade in ancient manuscripts. This paper aims to uncover how the practice of ancient manuscript trade in society and try to provide solutions. The research was conducted by interviewing the script seller and collector and the owner of the manuscript plus a literature review related to the problem. The results of the study show that many texts are stored in communities that have not been touched by philologists. Most people do not know the importance of the text while there are many requests for ancient texts. This situation was used by collectors who came from script traders and collectors to practice buying and selling texts.